2017
DOI: 10.4103/2229-516x.205806
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant thyroid gland diseases in the patients with primary hyperparathyroidism

Abstract: Introduction:This study aimed to evaluate concurrently detected thyroid pathologies in the patients who underwent surgery for primary hyperparathyroidism (PHPT).Materials and Methods:In this study, we retrospectively analyzed the files of the patients who underwent surgery for PHPT between 2012 and 2015. Pre- and post-operative laboratory examination results and preoperative radiological and nuclear medicine findings of the patients were retrospectively recorded.Results:A total number of 41 patients with PHPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…When we compared the patients with PTC with those who were with benign cytology, we found no difference in terms of demographic characteristics and clinical parameters. In three studies, two of which were conducted in Türkiye, no significant difference was found between benign and malignant groups in patients with hyperparathyroidism in terms of age, gender, preoperative PTH, Ca, P, 25-OH-D3, 24-hour urinary Ca levels (3,21,22) compatible to our study. In the study of Celik et al ( 22) also anti-TPO levels were compared and no significant difference was found similar to our study.…”
Section: Discussionsupporting
confidence: 84%
“…When we compared the patients with PTC with those who were with benign cytology, we found no difference in terms of demographic characteristics and clinical parameters. In three studies, two of which were conducted in Türkiye, no significant difference was found between benign and malignant groups in patients with hyperparathyroidism in terms of age, gender, preoperative PTH, Ca, P, 25-OH-D3, 24-hour urinary Ca levels (3,21,22) compatible to our study. In the study of Celik et al ( 22) also anti-TPO levels were compared and no significant difference was found similar to our study.…”
Section: Discussionsupporting
confidence: 84%
“…PTC is the most common type of the malignant thyroid lesions synchronous with PHPT [ 13 15 ]. Ogburn and Black were the first to report the concomitant PTC in PHPT patients in 1956 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the higher PTC prevalence in the asymptomatic PHPT patients in this inpatient cohort might be also caused by the selection bias, since patients with potential malignant thyroid lesions had higher possibility of hospitalization. PTC is the most common type of the malignant thyroid lesions synchronous with PHPT [13][14][15]. Ogburn and Black were the first to report the concomitant PTC in PHPT patients in 1956 [16].…”
Section: Discussionmentioning
confidence: 99%